2013
DOI: 10.1155/2013/935852
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Glucose from Residual Starch of Sago Hampas for Bioethanol Production

Abstract: Lower concentration of glucose was often obtained from enzymatic hydrolysis process of agricultural residue due to complexity of the biomass structure and properties. High substrate load feed into the hydrolysis system might solve this problem but has several other drawbacks such as low rate of reaction. In the present study, we have attempted to enhance glucose recovery from agricultural waste, namely, “sago hampas,” through three cycles of enzymatic hydrolysis process. The substrate load at 7% (w/v) was seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 28 publications
3
41
2
2
Order By: Relevance
“…Sago pith flour, as a part of the dry extraction production, contains a high amount of starch (86%), while, as a by-product from the inefficient wet extraction process, sago hampas contains approximately 55% starch and 15% fiber on a dry weight basis. Composition of this sago hampas was similar to that reported by Lingga et al (2012) which showed 58% starch, compared to Awg- Adeni et al (2013) who reported a lower starch content (30-45%) and higher fiber content (30-35%).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Sago pith flour, as a part of the dry extraction production, contains a high amount of starch (86%), while, as a by-product from the inefficient wet extraction process, sago hampas contains approximately 55% starch and 15% fiber on a dry weight basis. Composition of this sago hampas was similar to that reported by Lingga et al (2012) which showed 58% starch, compared to Awg- Adeni et al (2013) who reported a lower starch content (30-45%) and higher fiber content (30-35%).…”
Section: Resultssupporting
confidence: 84%
“…Linggang et al (2012) reported that sago pith waste contains 58% starch, 23% cellulose, 9.2% hemicellulose, and 4% lignin on a dry basis. Awg- Adeni et al (2013) state that on a dry basis, the proportions of sago pith waste consist of 30-45% starch, 5-7% ash, 1% protein, and 4.6-4.7% fiber. Several studies have been done on utilizing sago pith waste as a substrate for the production of enzymes and adsorbents , glucose syrup (Asben et al 2011;Linggang et al 2012), fructose syrup (Mishima et al 2011), bioethanol (Awg-Adeni et al 2011Peristiwati et al 2011), and biobutanol (Linggang et al 2011;).…”
Section: Problems Of Sago Starch Extractionmentioning
confidence: 99%
“…Sago pith flour, as a part of the dry extraction production, contains a high amount of starch (86%), while, as a by-product from the inefficient wet extraction process, sago hampas contains approximately 55% starch and 15% fiber on a dry weight basis. Composition of this sago hampas was similar to that reported by Lingga et al (2012) which showed 58% starch, compared to Awg-Adeni et al (2013) who reported a lower starch content (30-45%) and higher fiber content (30-35%).…”
Section: Introductionsupporting
confidence: 84%
“…At the maximum substrate concentration of 6% (w/v), enzymatic hydrolysis under these optimum conditions generated 30 g/L of sugars or a recovery of 50% from dried sago hampas (Janggu and Bujang 2009). Adeni et al (2013) reported that recycling the hydrolysate in enzymatic hydrolysis of sago hampas for production of sugar greatly increased the yield from one cycle (27.8 g/L) to two cycles (73.0 g/L) and three cycles (138.5 g/L), a recovery of 70% from sago hampas (w/w). Fermentation of this sugar using baker's yeast generated 40.3 g/L of ethanol after 16 h or 93.3% theoretical yield based on glucose concentration.…”
Section: Production Of Sugars From Sago Hampasmentioning
confidence: 99%